Emotional intelligence and aggression among adolescents in Tehran, Iran - Masoumeh, Homauni; Mansor, Mariani; Yaacob, Siti Nor; Abu Talib, Mansor; Sara, Ghazizade (Marsland Press, 2014)
The purpose of this study was to examine the relationship between sub-components of emotional intelligence and the adolescent’s aggression among Iranian high schools students in Tehran, Iran. Emotional Intelligence (EQ) is a set of abilities such as conception, emotion appraisal and expression, emotion management and regulation, and emotion utilization of emotion. The present study was carried out among Iranian students. Number of respondents in the present study includes 200 (50%) males and 200 (50%) females from 20 high schools in Tehran, Iran. Respondents were between the ages of 16 to 18 years. Pearson correlation between subscales of aggression and emotional intelligence was statistically significant.